Verske svoboščine in položaj verskih skupnosti v ustavnopravnem sistemu Združenih držav Amerike - Lampe, Rok (Revus (Ljubljana), 2004)
The author's main focus is on the two "religion clauses" of the first amendment of the Constitution of the United States. These clauses - "the establishment clause" ("Congress shall make no law respecting an establishment of religion") and the "free exercise clause" ("Congress shall make no law ... prohibiting the free exercise thereof") are the crucial aspects of the "wall of separation" between the State and religion. Those clauses have been precisely defined by the US Supreme Court in its long practice. The basic "test" whether a State act is in accordance with the first amendment is in Lemon v. Kurtzman which established the Lemon test. According to this test (1) the Law or a State act must have a secular purpose, (2) the primary effect of it must be that it neither advances nor inhibits religion, and (3) it must not foster "excessive government entanglement" with religion. Only if a State act meets these standards does it not infringe the religion freedoms set out in the first amendment.
Keywords: človekove pravice; pravno varstvo; svoboda veroizpovedi; ustavno pravo; verske skupnosti; ZDA